Banking Sector in the Conditions of War: Features of State Regulation - Veretelnikov, Ihor (Theory and Practice of Public Administration, 2023)
The article theoretically substantiates the peculiarities of the banking sector as an object of state regulation and proposes directions and measures of state influence on ensuring the stability of the banking sector and its further development, taking into account the challenges caused by the full-scale invasion of the Russian Federation into Ukraine. It has been proven that an efficiently functioning banking sector is an important factor in the economic development of the state. Effective government regulation stimulates the attraction of capital into the economy, lending to enterprises and private individuals, promotes the development of financial instruments and services, and also regulates risks in the activities of banks both in the short term and in the long term. Thanks to the timely and prompt adoption of relevant legal acts aimed at stabilizing the banking sector, the country’s banking system withstood the war and continues to work. At the same time, there is a need for a systematic review of approaches to state regulation of this area, in particular, adjustment of its goals, objectives and implementation mechanisms in order to maintain the stability of the functioning of the banking system in the long term. In order to implement the principles of ensuring security and stability, ensuring liquidity and financial stability, regulatory flexibility, transparency and communication, protection of bank clients in the practice of state administration during a long war, it is proposed to apply a set of state measures. Measures are classified according to such directions as ensuring financial support for banks, ensuring cyber security in the face of increasing digital threats, regulatory support for banking activities, protecting the rights and interests of bank clients, establishing communication and cooperation channels. The importance of constant monitoring and flexible response to changes was emphasized in order to ensure the effective functioning of banks and protect the interests of all interested parties. In view of this, the direction of further research may be the development of a system of criteria for ongoing monitoring and final evaluation of the effectiveness of the application of measures of state regulation of the banking sector in terms of individual directions.